Patterned distributed populations: Beyond Turing: Comment on: “Phase separation driven by density-dependent movement: A novel mechanism for ecological patterns” by Quan-Xing Liu et al. - Kuperman, Marcelo Nestor (Elsevier Science, 2016)
Fil: Kuperman, Marcelo Nestor. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Area de Investigación y Aplicaciones No Nucleares. Gerencia de Física (Centro Atómico Bariloche); Argentina